2017
DOI: 10.15623/ijret.2017.0602019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tool Rotational Speed and Axial Load in Friction Stir Welding (Fsw) of High Strength Aluminum Alloys

Abstract: The aim of the present work was to study the effect of tool rotating speed, and axial load on microstructure, tensile properties, and hardness distribution of FSW butt joints of AA2024-T3 and AA7075-T6 Al-alloys

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They found that low axial force led to low heat and hydrostatic pressure under the shoulder which caused insufficient stirring of the metal in the joint, Sreenivas et al [33] concluded that using an axial force more than 4 kN to joint 6082-T6 plates reduced the tensile strength. Mahany et al [34] noticed that among the axial force (1000, 1150, 1300, and 1400 kN), the 1300 kN axial force produced the highest tensile strength joint of 7075-T6 and 2024-T6 plates. Increasing the axial force increased the grain size and hardness as a result of good stirring of the metal in the joint.…”
Section: Fig 4 Axial Loadmentioning
confidence: 99%
“…They found that low axial force led to low heat and hydrostatic pressure under the shoulder which caused insufficient stirring of the metal in the joint, Sreenivas et al [33] concluded that using an axial force more than 4 kN to joint 6082-T6 plates reduced the tensile strength. Mahany et al [34] noticed that among the axial force (1000, 1150, 1300, and 1400 kN), the 1300 kN axial force produced the highest tensile strength joint of 7075-T6 and 2024-T6 plates. Increasing the axial force increased the grain size and hardness as a result of good stirring of the metal in the joint.…”
Section: Fig 4 Axial Loadmentioning
confidence: 99%